Production and characterisation of nanoemulsions stabilised by sophorolipids produced from different secondary substrates - Leow, Yew Seng (2022)
Sophorolipids (SLs) produced from Starmerella bombicola are among the most extensively researched glycolipids biosurfactants. SLs surfactants are preferred over their chemical counterpart due to their intrinsic properties such as high biodegradability, environmentally friendly, low toxicity and excellent surface activities. However, their production is still inferior to the chemical surfactants and their performance as emulsifier are poor. There are also increasing awareness pertaining the usage of natural ingredients in commercial products as a part of sustainable greener alternative effort. Hence, this study aims to use a more affordable raw material to produce SLs which subsequently will be used as a stabiliser for nanoemulsions. Four main secondary substrates were used for production of SLs via fermentation of S. bombicola. These included vegetable oils such as refined, bleached and deodorised palm olein (RBD PO), RBD palm kernel olein (RBD PKO), and RBD coconut olein (RBD CO) and new palm-based waste known as fatty acid methyl ester (FAME) waste. These substrates were supplemented at 10 % v/v into the fermentation medium of S. bombicola. After cultivation of S. bombicola for 8 days, the highest SLs yield of 32.05 g/L was obtained from fermentation using RBD PO followed by RBD PKO, RBD CO and FAME waste at 11.91 g/L, 10.34 g/L and 6.51 g/L respectively. The reason was RBDPO was rich in C16 and C18 fatty acids. Fatty acid chain length of SLs produced from RBD PO and FAME waste were mainly of C16 and C18 while SLs from RBD PKO and RBD CO consisted mainly C12. All SLs produced from the various substrates exhibited surface tension reducing properties of water from 72 mN/m to a range between 33.64 and 36.98 mN/m. Critical micelle concentration values (CMC) of SLs from RBD PO, RBD PKO, RBD CO and FAME waste were 90 mg/L, 120 mg/L, 120 mg/L and 40 mg/L, respectively. The SLs were also able to displace medium chain triglyceride (MCT) oil with a diameter ranging from 2.2 to 3.45 cm. In addition, emulsification activity towards MCT oil shown by the SLs was from 20.45 to 44.70%. SLs were also studied for their antimicrobial activity towards Bacillus cereus and Pseudomonas aeruginosa. The inhibition zone was determined for B. cereus with diameters ranging from 7.70 to 14.54 cm, but no antimicrobial activity was observed for SLs towards P. aeruginosa. SLs were then used in the formulation of nanoemulsions blends (coded F1 to F9) in which F1 formulation was with soybean lecithin as sole surfactant, F2 to F5 with SLs as sole surfactant, and F6 to F9 with mixture of SLs and soybean lecithin as the second emulsifier. The nanoemulsions were made using homogenisation and ultrasonication methods. Results showed F1, F6, F7, F8 and F9 exhibited a good stability while F2, F3, F4 and F5 displayed not only unsatisfactory stability but also very large particle size exceeding nano-scale range. Among the formulations, F9 had the smallest average particle size (236 nm) with the zeta potential value of – 61.7 mV. Meanwhile, formulation F6 bigger average particle sizes (391 nm) with zeta potential value of – 75.2 mV. Formulation blends (F6 to F9) exhibited a stable emulsion in which they can withstand thermal processing from 40 oC to 90 oC and pH range from pH 3 to pH 9. However, these formulations were susceptible to salt concentration range of 10 mM to 300 mM when phase separations were observed. All formulation blends showed good stability during storage stability at 4 oC and 25 oC. At elevated temperature of 40 oC, only F6 and F9 retained their high stability because their particle sizes remained relatively constant over the period of 30 days. However, changes in the average particle size were observed in F1, F7 and F8 over time. All of the nanoemulsions showed antimicrobial activity towards B. cereus and P. aeruginosa. Their antioxidant activities are low in the range 37 to 46% with the highest activity observed in F6 at 45.62%. Additionally, they were found to be cytotoxic towards human epithelial colorectal adenocarcinoma (Caco2) cell line with the lowest concentration to inhibit 50% of the cells (IC50) of 35 μg/mL for F1 followed by F7, F8, F9 and F6 with IC values of 65, 70, 85 and 35 μg/mL, respectively. In conclusion, RBDPO was a more superior SLs feedstock while FAME waste was the sustainable substrate for SLs production. The SLs developed in this study exhibit excellent surface properties, CMC, surface-tension reducing abilities and antimicrobial activity. Nonetheless, their poor emulsifying performance forms unstable emulsion when they are used as a sole emulsifier. So, nanoemulsions can be produced using a mixture of SLs and soybean lecithin which showed greater stability towards temperature and pH stress but were unable to withstand low salt concentration. They also exhibited the antimicrobial and cytotoxic activity.